Volatility Transmission in Crude Oil, Gold, S&P 500 and US Dollar Index Futures Using VAR-MGARCH Model - Bunnag, Tanattrin (International Journal of Energy Economics and Policy, 2016)
This paper examined volatility transmission in the crude oil, gold, S&P 500 and US Dollar Index futures. The data used in this study was the daily data from 2010 to 2015. The four VAR- MGARCH models, namely the VAR (2)-diagonal VECH, the VAR (2)-diagonal BEKK, the VAR (2)-CCC and the VAR (2)-DCC, were employed. The empirical results showed that the estimates of the VAR (2)-diagonal BEKK parameters were statistically significant in all cases. Later, the VAR (2)-diagonal VECH parameter were statistically significant in case of RCRUDE with RGOLD, RGOLD with RSP and RSP with RUSD. At the same time the VAR (2)-CCC parameters were statistically significant in only case of RCRUDE with RGOLD. Finally, the VAR (2)-DCC were statistically significant in case of RCRUDE with RGOLD, RGOLD with RSP, RGOLD with RUSD and RSP with RUSD. In addition, we could conclude that the crude oil futures volatility was having an impact on the gold futures volatility, the gold futures volatility was having an impact on S&P 500 futures volatility, the gold futures volatility was having an impact on US Dollar Index futures volatility and S&P 500 futures volatility was having an impact on US Dollar Index futures volatility. Keywords: volatility transmission; VAR-MGARCH JEL Classifications: C13; C32; G13